Serum pepsinogen I and II concentrations and IgG antibody to Helicobacter pylori in dyspeptic patients. Issue 9 (September 1993) - Biasco, G; Paganelli, G M; Vaira, D; Holton, J; Di Febo, G; Brillanti, S; Miglioli, M; Barbara, L; Samloff, I M
Abstract : AIMS--To investigate the association between histologically confirmed gastritis, carriage of Helicobacter pylori and pepsinogen (PG) I and PG II concentrations. METHODS--Prospective study of 81 dyspeptic patients undergoing upper gastrointestinal endoscopy was made. The extent of gastric mucosal inflammation and the presence of H pylori was determined, and serology to evaluate PG I and II concentrations and IgG titres to H pylori was carried out. RESULTS--The presence of H pylori was strongly correlated with high IgG antibody titres to H pylori and gastritis. Patients who were H pylori positive had significantly higher PG I and PG II concentrations and a significantly lower PG I:PG II ratio than patients who were negative for H pylori. In 13 patients with duodenal ulcer and H pylori positive gastritis serum PG I concentrations were significantly higher than in H pylori positive patients without duodenal ulcer. Significant correlations were found between the age of patients and serum PG II, the PG I:PG II ratio, IgG antibodies to H pylori, the severity of body gastritis and H pylori infection, and between the degree of gastritis in the body of the stomach and the PG II concentration. CONCLUSIONS--Serum PG I and II concentrations, together with a fall in the PG I:PG II ratio, could be used as predictors of H pylori infection as well as serum IgG antibody response to H pylori.